Two byzantine lives of st. John Chrysostom of 10 century and their sources - Balakhovskaia Aleksandra (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ III. Filologiâ, 2012)
Among numerous Byzantine Lives of St. John Chrysostom there are two, which are very similar. Both of them were written in the middle of 10 century, and one can come across the same phrases and expressions in them. One of them is longer and contains many additional details. How can we explain this phenomenon? Was the shorter Life the source of the other or did they both have a common source? The article attempts to answer this question.